Simulation Of Preventive Maintenance Schedule In Reducing Machine Stoppage And Downtime - Mak, Kam Sheng (Universiti Sains Malaysia, 2018)
In the past several decades, there have been diverse and significant research activities on maintenance scheduling. Machines are usually down periods due to plenty of reasons such as preventive maintenance activities. Preventive maintenance is defined as regularly scheduled maintenance actions based on the average failure rates. An optimize implemented preventive maintenance strategy can provide many benefits to an organization in terms of extending equipment life and machine availability. Few researches have addressed the issues of preventive maintenance. For instances, proper preventive maintenance scheduling can maximize the machine lifecycle and production throughputs. In this thesis, the objective is to study the machine availability that affected by the preventive maintenance scheduling. The model was developed based on the Surface Mounted Technology (SMT) in manufacturing system. The SMT line is a continuous flow production line since every machine are connected in line. In this research, the model that has been build consists of five different machine which is screen printer, glue dispenser, chip shooter, pick and place and reflow oven. WITNESS 14 Manufacturing Performance Edition software was used to imitate the Surface Mounted Technology (SMT) production system. This is to carry out the optimisation of preventive maintenance scheduling by using different breakdown intervals and preventive maintenance duration. Results of simulation study comparing the availability of machine with different preventive maintenance scheduling. The total system availability was calculated since the SMT line is continuous flow production. The findings of this project shown that the optimise preventive maintenance should be done every one week with 30 minutes PM duration.